CAPACITY FOR MATHEMATICAL LITERACY REVIEWING THE LEARNING STYLE - Qolbi, Anisa Nur; Afriansyah, Ekasatya Aldila (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2024)
The ability to read and write mathematically is crucial for all students because it allows one to comprehend the importance of mathematics in daily life. Since Indonesian students still have very poor levels of mathematics literacy, the educational process needs to be improved. In order to facilitate the learning process and attain mathematical literacy, students must be aware of their preferred learning style. The purpose of this study is to ascertain the relationship between learning methods and mathematical literacy competence. Qualitative research is the approach used in this study. Purposive sampling was utilized to choose the research subjects for this study, and two junior high school students were chosen for each of the three learning styles—visual, auditory, and kinesthetic—based on the findings of their assessments.